Peran Keuangan Sosial Islam dalam Mencapai Sustainable Development Goals - Alfian, Annisa Maulidia; Jaswil, Irwandi; Wira, Ahmad; Novia, Aidil (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Islamic social finance (ISF) plays an important role in achieving sustainable development goals (SDGs) through financing mechanisms based on fair, transparent, and inclusive sharia principles. This article aims to explore the contribution of ISF to the achievement of the SDGs, focusing on how Islamic financial instruments, such as zakat, waqf, sedekah, and sukuk, can help address global challenges, especially in terms of poverty alleviation, social equity, and environmental sustainability. Through a literature review and analysis of various case studies, this study shows that ISF can not only accelerate the achievement of economic goals but also significantly improve social welfare and environmental sustainability. With its foundation of social justice and welfare distribution, Islamic social finance provides an effective alternative in creating economic inclusion, redressing social inequality, and supporting environmentally friendly sustainability programs. This study also identifies challenges and opportunities in optimizing the role of ISF in the context of the SDGs. It provides policy recommendations to enhance synergy between the Islamic financial sector and the implementation of the SDGs.